A Study of Components and Guidelines for Monitoring and Evaluation of Student Support System Operations under Roi Et Primary Educational Service Area Office 3 - Raksura, Promboon (Arts of Management Journal, 2026)
This research aimed to 1) study the components of monitoring and evaluating the student support system and 2) study the guidelines for monitoring and evaluating the student support system under the Roi Et Primary Educational Service Area Office 3. The target group consisted of 422 school administrators and teachers responsible for the student support system from 211 schools, selected using stratified random sampling and simple random sampling within each stratum. The instruments used included a component assessment form and a semi-structured interview. The statistics used were mean, frequency, percentage, standard deviation, and content analysis. The research findings revealed that 1) the monitoring and evaluation components of the student support system consist of four elements: context, input, process, and outcome, with a total of 15 sub-components; and 2) the monitoring and evaluation guidelines should be implemented by all stakeholders, covering all four components, using a systemic approach consistent with the policies of the supervising agency. Furthermore, the components evaluated for appropriateness by five experts had an overall average score at the highest level ( =4.68, S.D.=0.47). These research findings provide important data for developing future monitoring and evaluation models.